Penerapan Teori Permainan untuk Strategi Bisnis Perusahaan Jasa Pengiriman Barang : Studi Kasus: Persaingan JNE dan J&T Lingkup Mahasiswa Universitas Sumatera Utara - Fitria Riyadi; Elly Rosmaini (Lembag, 2026)
The development of modern times is marked by the increasing number of companies that facilitate people’s daily activities, one of which is freight forwarding service companies. This condition has led to increasingly intense competition among delivery service companies, requiring each company to implement appropriate strategies in order to maintain its existence and win the competition. One method that can be used to analyze marketing competition strategies is game theory. Game theory is a mathematical concept used to analyze decision-making in competitive situations involving two opposing parties. This study aims to analyze the competition between JNE and J&T using a game theory approach. The method employed is linear programming with the assistance of the POM QM 5.0 application to determine the optimal strategies for each company. The results show that the optimal game value obtained is -1.715. Under these conditions, the optimal strategy for JNE involves a mixed strategy consisting of pricing, delivery estimation, and service security strategies. Meanwhile, the optimal strategy for J&T involves a combination of delivery punctuality, service security, and online application strategies.